Youth Drug Offenders: An Examination of Criminogenic Risk and Juvenile Recidivism. Issue 4 (1st October 2016) - Papp, Jordan; Campbell, Christina; Onifade, Eyitayo; Anderson, Valerie; Davidson, William; Foster, Dawn
ABSTRACT: Understanding risk factors and treatment needs of juvenile drug offenders is important because of the myriad negative outcomes that befall juveniles involved in drugs. The Youth Level of Service/Case Management Inventory was used to explore differences between drug and nondrug offenders. Results suggested that substance use was not predictive of recidivism for juvenile drug offenders. However, peer relationships and attitudes significantly predicted recidivism for drug offenders, suggesting that case planners should pay particular attention to these domains when designing treatment plans. Cox Regression Hazard Modeling was used to estimate risk for recidivism. Results revealed that while juvenile drug offenders had a significantly higher score for substance use, juvenile drug offenders did not have increased risk for recidivate than nondrug offenders.